A global study of satellite observations of clouds in the Tropics and their relationship with dew point temperatures - RAMASWAMY, C. (MAUSAM, 1971)
Charts showing isopleths of long-term monthly mean dew points over the world at sea level between 75o N and 65oS have been prepared for the months January, April, July and October. The isopleths on these charts between 30oN and 30oS have been compared with the isopleths of average cloudiness based on satellite observations of 2 years over the same range of latitudes. It has been shown that the sea level dew point isopleths have a high correlation with the cloudiness gradients and the orientation of the isopleths of cloudiness in the tropics in the northern as well as the southern hemispheres. A general examination has also been made of the isopleths of dew points over the northern hemisphere at the 850 and 700-mb levels as available in recent published literature for the months January and July. It is has been found that the isopleths at the 850-mb level resemble those at sea level in regard to their orientation and thus resemble the isopleths of average cloudiness, although to a less satisfactory extent than the sea level patterns. The patterns at the 700-mb level differ appreciably from those at the 850-mb level particularly north of 15o N. The significance of these factual findings and the possible usefulness of the dew point temperatures in studies of the moisture-field and the water-budget of the atmosphere are discussed.